Comprehensive Support for Family Caregivers of Post-9/11 Veterans Increases Veteran Utilization of Long-term Services and Supports: A Propensity Score Analysis. (27th March 2018) - Shepherd-Banigan, Megan; Smith, Valerie A.; Stechuchak, Karen M.; Miller, Katherine E. M.; Hastings, Susan Nicole; Wieland, Gilbert Darryl; Olsen, Maren K.; Kabat, Margaret; Henius, Jennifer; Campbell-Kotler, Margaret; Van Houtven, Courtney Harold
Family caregivers are an important component of the long-term services and supports (LTSS) system. However, caregiving may have negative consequences for caregiver physical and emotional health. Connecting caregivers to formal short-term home- and community-based services (HCBS), through information resources and referrals, might alleviate family caregiver burden and delay nursing home entry for the patient. The aim of this study was to evaluate the early impact of the Program of Comprehensive Assistance for Family Caregivers (PCAFC) (established by P.L. 111-163 for family caregivers of seriously injured post-9/11 Veterans) on Veteran use of LTSS. A two-cohort pre-post design with a nonequivalent comparison group (treated n = 15 650; comparison n = 8339) was used to (1) examine the association between caregiver enrollment in PCAFC and any VA-purchased or VA-provided LTSS use among Veterans and (2) describe program-related trends in HCBS and institutional LTSS use. The comparison group was an inverse-propensity-score weighted sample of Veterans whose caregivers applied for, but were not accepted into, the program. From baseline through 24 months post application, use of any LTSS ranged from 13.1% to 17.8% for Veterans whose caregivers were enrolled in PCAFC versus from 3.8% to 5.3% for Veterans in the comparison group. Participation in PCAFC was associated with a statistically significant increased use of any LTSS from 1 to 24 months post application (over time odds ratios ranged from 2.71 [95% confidence interval: 2.31-3.17] to 4.86 [3.93-6.02]). Support for family caregivers may enhance utilization of LTSS for Veterans with physical, emotional, and/or cognitive conditions.